OCCUPATIONAL EXPOSURE LIMITS FOR CHEMICALS. Issue 2 (1st February 2001) - Topping, M
Abstract : ▸ Occupational exposure limits (OELs) are tools to help employers protect the health of those who may be exposed to chemicals in their workplace. Under the United Kingdom Control of Substances Hazardous to Health (COSHH) Regulations they define adequate control by inhalation. ▸ OELs are set by the Health and Safety Commission (HSC) on advice from its Advisory Committee on Toxic Substances (ACTS) and after public consultation. Thus they are consensus limits which have the support of both sides of industry. ▸ COSHH uses two types of occupational exposure limit—the occupational exposure standard (OES) and the maximum exposure limit (MEL). ▸ OESs are set for substances for which it is possible to identify a concentration at which there is no significant risk to health. Employers are required to meet the limit, there is no requirement to go below it, and it can be exceeded provided steps are taken to meet it as soon as reasonably practicable. ▸ MELs are set for substances which have serious health implications and for which an OES cannot be set. Most of the substances with MELs are either carcinogens or causes of occupational asthma. Employers must not exceed an MEL and must reduce exposure as far below it as is reasonably practicable. ▸ MELs are set at concentrations achievable by good occupational hygiene practice such that risks to workers are judged to be reduced to a tolerable level. The HSC consider that this approach is preferable to the use of mathematical models to generate risk estimates, which inevitably gives a spurious appearance of accuracy. ▸ The MEL/OES system is poorly understand by many employers who use chemicals, is not comprehensive as some substances meet neither the OES nor MEL criteria, and does not mesh well with indicative occupational exposure limit values which will increasingly be set under the European Union Chemical Agents Directive. ▸ COSHH essentials: easy steps to control chemicals provides the practical help that firms need to control chemicals. It takes users straight from hazard and exposure considerations to benchmark standards of good practice. ▸ The problems with the current system have prompted ACTS to set up a subgroup to review the OEL framework.